To stop or to permit? Unobvious effects of suburbanization. Studies of the rural communes in the vicinity of Olsztyn - Źróbek-Różańska, Alina; Wolny, Ada (Uniwersytet Opolski, 2020)
Suburbanization means acontroversial process and many authors often underline its negative consequences. This paper is aimed at presenting its unobvious effects on the basis of local studies. The relevant analyses were conducted with the descriptive method, complemented with calculations and nuclear estimation. It was observed that suburban residential development can be concentrated along existing infrastructural facilities and the new investments are along-term process, thus new settlements do not mean additional expenditures in ashort term. However, apositive consequence of suburbanization is, among others, increasing financial incomes in the commune’s budget or shifting the traffic to roads with better capacity. There are also benefits for the inhabitants, such as improvement of the living space. Suburbanizacja to proces wzbudzający wiele kontrowersji, aautorzy opracowań często podkreślają jej negatywne konsekwencje. Celem niniejszego opracowania jest ukazanie jej nieoczywistych skutków przy uwzględnieniu badań lokalnych. Posłużono się m.in. metodą opisową, uzupełnioną obliczeniami, atakże metodą estymacji jądrowej. Jak wynika zobserwacji, zabudowa podmiejska może być skoncentrowana przy istniejących urządzeniach infrastrukturalnych, arealizacja nowych inwestycji to proces wieloletni, nie powodujący zatem konieczności ponoszenia nakładów wkrótkim czasie. Pozytywnym następstwem suburbanizacji może być natomiast wzrost wpływów budżetowych wgminach podmiejskich oraz przesuniecie ruchu na drogi owiększej przepustowości. Ponadto korzyści odnoszą sami mieszkańcy wwyniku poprawy jakości przestrzeni mieszkalnej.